2020
DOI: 10.3102/1076998620972800
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Weight Estimation of Latent Ability: Application to Computerized Adaptive Testing With Response Revision

Abstract: An adaptive weight estimation approach is proposed to provide robust latent ability estimation in computerized adaptive testing (CAT) with response revision. This approach assigns different weights to each distinct response to the same item when response revision is allowed in CAT. Two types of weight estimation procedures, nonfunctional and functional weight, are proposed to determine the weight adaptively based on the compatibility of each revised response with the assumed statistical model in relation to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, scoring based on the number of attempts instead of first‐attempt correctness also improves measurement reliability for target ability (Attali & Powers, 2010; Bergner et al., 2019). Recent studies on computerized adaptive testing (CAT) allowing for response review also suggested that more information regarding examinees' proficiency and test‐taking behavior can be gained compared with CAT without such a design feature (Wang et al., 2021). On the other hand, allowing response revision and review remarkably complexifies the observed data structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, scoring based on the number of attempts instead of first‐attempt correctness also improves measurement reliability for target ability (Attali & Powers, 2010; Bergner et al., 2019). Recent studies on computerized adaptive testing (CAT) allowing for response review also suggested that more information regarding examinees' proficiency and test‐taking behavior can be gained compared with CAT without such a design feature (Wang et al., 2021). On the other hand, allowing response revision and review remarkably complexifies the observed data structure.…”
Section: Introductionmentioning
confidence: 99%
“…When a CBT allows reviews, revision behavior can often explicitly or implicitly influence a test taker's or a subgroup's performance. In some measurement models, answer change trajectory is explicitly used for scoring (e.g., Attali & Powers, 2010; Wang et al., 2021). Revision behaviors may also implicitly affect an individual's score.…”
Section: Introductionmentioning
confidence: 99%